2012
DOI: 10.1016/j.ajpath.2011.10.025
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic Bacteria Induce Maturation of Intestinal Claudin 3 Expression and Barrier Function

Abstract: An immature intestinal epithelial barrier may predispose infants and children to many intestinal inflammatory diseases, such as infectious enteritis, inflammatory bowel disease, and necrotizing enterocolitis. Understanding the factors that regulate gut barrier maturation may yield insight into strategies to prevent these intestinal diseases. The claudin family of tight junction proteins plays an important role in regulating epithelial paracellular permeability. Previous reports demonstrate that rodent intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
247
5
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(269 citation statements)
references
References 61 publications
14
247
5
3
Order By: Relevance
“…Claudin 3 is a tightening TJ protein that aids in sealing of the paracellular intestinal barrier, and impaired expression may lead to intestinal disease in mice [74]. In vertebrate, claudin-7 could also play a role in tightening of epithelial barriers [74]. Surprisingly, our results showed that Ile deficiency up-regulated gene expressions of occludin, claudin-3 and claudin-7 in the intestine of Jian carp.…”
Section: 4contrasting
confidence: 49%
See 1 more Smart Citation
“…Claudin 3 is a tightening TJ protein that aids in sealing of the paracellular intestinal barrier, and impaired expression may lead to intestinal disease in mice [74]. In vertebrate, claudin-7 could also play a role in tightening of epithelial barriers [74]. Surprisingly, our results showed that Ile deficiency up-regulated gene expressions of occludin, claudin-3 and claudin-7 in the intestine of Jian carp.…”
Section: 4contrasting
confidence: 49%
“…In vitro, down-regulation of occludin gene blocked the formation of the paracellular seal in human epidermal keratinocytes [73]. Claudin 3 is a tightening TJ protein that aids in sealing of the paracellular intestinal barrier, and impaired expression may lead to intestinal disease in mice [74]. In vertebrate, claudin-7 could also play a role in tightening of epithelial barriers [74].…”
Section: 4mentioning
confidence: 99%
“…For example, in experimental models of colitis, several species of probiotics including Lactobacillus, Escherichia coli, and Bifidobacterium can reduce gut permeability by upregulating trans-membrane proteins that are important in preserving tight junctions between epithelial cells. [30][31][32][33] It has also been shown that treatment with these probiotics can enhance mucus production and consequently improve the physical barrier protecting the epithelial layer. 34,35 Products of bacterial fermentation can also play an important role in maintaining the intestinal barrier.…”
Section: Effect Of Gut Microbiota On Intestinal Permeabilitymentioning
confidence: 99%
“…However, alteration of gut flora is only one potential mechanism by which probiotics might prevent NEC. Other mechanisms include effects on the gut immune system and via TLR-related signaling [76,77] and effects on mucosal integrity and intestinal permeability [78,79]. However, whether these are primary or secondary effects is extremely difficult to dissect, as the microbiome, immune system, mucosal integrity and gut barrier function are all mutually interdependent.…”
Section: Mechanistic Basic Science Studies On Probioticsmentioning
confidence: 99%